Effects of Zentangle art workplace health promotion activities on rural healthcare workers. (July 2021) - Hsu, M.f.; Wang, C.; Tzou, S.J.; Pan, T.C.; Tang, P.L.
Abstract: Objectives: Workplace health promotion activities have a positive effect on emotions. Zentangle art relaxes the body and mind through the process of concentrating while painting, achieving a healing effect. This study aimed to promote the physical and mental health of rural healthcare workers through Zentangle art–based intervention. Study design: This was a quasi-experimental pilot study. Methods: A Zentangle art workshop was held from November 2019 to July 2020. A total of 40 healthcare workers were recruited. The participants were asked to provide baseline data, and the Brief Symptom Rating Scale (BSRS-5), work stress management effectiveness self-rating scale, General Self–Efficacy Scale (GSES), and Workplace Spirituality Scale (WSS) were administered before and after the workshop. SPSS 22.0 statistical package software was used to conduct the data analysis. Results: The median age (interquartile range [IQR]) was 32.00 years (23.00–41.75 years). The Wilcoxon signed-rank test revealed that the median (IQR) BSRS-5 postintervention score was 4.0 (1.25–5.0), which was lower than the preintervention score ( P = 0.004). The postintervention score for the work stress management effectiveness self-rating scale was 36.5 (31.0–40.0), which was also lower than the preintervention score ( P = 0.009). A higher score for the GSES or WSS indicated improvements in stress management and self-efficacy. The GSES postintervention score 25.00 (21.0–30.75) was significantly higher than the preintervention score ( P = 0.010), and the WSS postintervention score 104.0 (88.0–111.75) was significantly higher than the preintervention score ( P = 0.005). Conclusions: The study provides evidence that painting therapy can effectively relieve stress, reduce workplace stress and frustration, enhance self-efficacy, and increase commitment to work among healthcare workers, thus improving their physical, mental, and spiritual well-being. Zentangle art provides employees with multiple channels for expressing their emotions and can improve the physical and mental health of healthcare workers in the workplace. It is beneficial and cost-effective and can serve as a benchmark for peer learning.